Leadership structure and value relevance during corporate governance reform / Adibah Jamaluddin, Nor ’Azam Mastuki and Asyaari Elmiza Ahmad - Jamaluddin, Adibah; Mastuki, Nor ’Azam; Ahmad, Asyaari Elmiza (Universiti Teknologi MARA, Shah Alam, 2011)
The sample of this study consists of Main Board companies listed on Bursa Malaysia from 1999 to 2001. This study investigates the effect of the issuance of the Malaysian Code on Corporate Governance (MCCG) on value relevance of accounting number. The main objective of this paper is to examine the effect of leadership structure on the value relevance of equity book value and earnings following the corporate governance reform by employing the Ohlson (1995) Valuation Model and based on the methodology developed by Davis-Friday et al. (2006). The findings generally indicate that equity book value and earnings are value relevant in assisting investors to value firms’ equity. Mixed results for leadership structure were found where the value relevance of equity book value increase whilst the value relevance of earnings decrease when companies practice duality structure in 2000. It, therefore, implies that the role of CEO and Chairman of the board should be separated in order to improve the value relevance of earnings. In summary, the findings of this study provide evidence that the equity book value and earnings reported in the financial statement is value relevant in valuing Malaysian firms’ equity. More importantly, the recommendation by the MCCG to practice unitary leadership